ANCA-Negative Granulomatosis with Polyangiitis Presenting with Hypertrophic Cranial Pachymeningitis, Abducens Nerve Palsy, and Stenosis of the Internal Carotid Artery. (30th November 2017) - Harabuchi, Shohei; Bandoh, Nobuyuki; Yasukawa, Rika; Kono, Michihisa; Goto, Takashi; Harabuchi, Yasuaki; Ikeda, Hidetoshi; Kamada, Hajime; Nishihara, Hiroshi
Abstract : We report a rare case of granulomatosis with polyangiitis (GPA) presenting with hypertrophic cranial pachymeningitis (HCP), abducens nerve palsy, and stenosis of the internal carotid artery (ICA). A 59-year-old Japanese man presented with a year history of nasal obstruction and a 2-month history of slight headache. Histopathological examination of the granulomatous mucosa in the ethmoid sinuses resected by endoscopic sinus surgery revealed necrotizing vasculitis with multinucleated giant cells. The patient was diagnosed with the limited form of GPA as a result of the systemic examination. He declined immunosuppressive treatment. Eighteen months after the diagnosis of GPA, he presented with diplopia and severe headache. Though nasal findings indicating GPA were not observed in the nasal cavity, CT scan revealed a lesion of the right sphenoid sinus eroding the bone of the clivus. Gadolinium-enhanced MRI of the brain showed thickening of the dura mater around the right cavernous sinus and clivus. Magnetic resonance angiography and cerebral angiography revealed narrowing at the C5 portion of the ICA. Intravenous methylprednisolone pulse therapy followed by oral prednisolone and cyclophosphamide resolved headache and dramatically improved HCP and stenosis of the ICA.